THE PLACE OF THE DIPLOMATIC PROTOCOL IN THE DEVELOPMENT OF INTERNATIONAL ECONOMIC RELATIONS - VORONOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The beginning of the new millennium demonstrates the plunge of the modern world into an era of deep interdependence. The global economy and advanced technologies are blurring borders and distances. The main task now is to strengthen the positive forces of interdependence and minimize negative risks. A constructive dialogue should take place in order to solve problems in various spheres of life. Overcoming the economic crisis, combating global warming, poverty, disease and the lack of educational opportunities, increasing security and reducing religious, cultural and ideological conflicts requires enormous international cooperation, in which diplomacy and the competent application of diplomatic protocol will play a key role. In the modern conditions of the development of international economic relations between states, the importance of diplomatic means of ensuring such relations is increasing, a special place among which belongs to the diplomatic protocol. The purpose of the scientific article is to highlight the place of the diplomatic protocol in the development of international economic relations. It was revealed that economic diplomacy is a special sphere of the system of international economic relations. It has been established that the diplomatic protocol plays an important role in the implementation of economic democracy. It was found that the diplomatic protocol is a set of rules, traditions and customs followed by governments, ministries of foreign affairs, diplomatic missions and other officials during international communication. It was determined that the basis of the diplomatic protocol is the rules of international courtesy established by the Vienna Convention on Diplomatic Relations of 1961. It was revealed that the rules and regulations of the diplomatic protocol regulate almost all forms of foreign policy and international economic cooperation. It is established that diplomatic etiquette and ceremonial are organic parts of diplomatic protocol. It is found that the practical significance of diplomatic etiquette is that at different levels of communication, which must be documented, established forms of common courtesy can be used without much effort in communication. It was determined that the provisions of the democratic protocol in the field of foreign economic activity provide the business world with universal and generally recognized rules of conduct, promote mutual understanding between representatives of different countries, make their communication harmonious, pleasant and useful, actively contribute to the development of the political, economic and socio-cultural environment. It was revealed that in international diplomatic contacts a special place is given to the diplomatic protocol. Diplomatic protocol regulates international economic relations and diplomatic practice, is based on international principles of courtesy and is carried out with the help of norms and etiquette.